2016
DOI: 10.1016/j.carbon.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Successful functionalization of superporous zeolite templated carbon using aminobenzene acids and electrochemical methods

Abstract: A novel and selective electrochemical functionalization of a highly reactive superporous zeolite templated carbon (ZTC) with two different aminobenzene acids (2-aminobenzoic and 4-aminobenzoic acid) was achieved. The functionalization was done through potentiodynamic treatment in acid media under oxidative conditions, which were optimized to preserve the unique ZTC structure. Interestingly, it was possible to avoid the electrochemical oxidation of the highly reactive ZTC structure by controlling the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…Nevertheless, the role of the different N functionalities still is not fully understood. Nitrogen-doped carbons can be synthesized following two different strategies: (i) by using a nitrogen-containing precursor as source or (ii) through post-treatments of a carbon material with nitrogen reagents [21,22]. However, these approaches usually require the use of high temperatures that would damage the fragile porous network of ZTCs.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the role of the different N functionalities still is not fully understood. Nitrogen-doped carbons can be synthesized following two different strategies: (i) by using a nitrogen-containing precursor as source or (ii) through post-treatments of a carbon material with nitrogen reagents [21,22]. However, these approaches usually require the use of high temperatures that would damage the fragile porous network of ZTCs.…”
Section: Introductionmentioning
confidence: 99%
“…Aqueous-based electrolytes are the best suited in this sense, although their small stability potential window have traditionally hampered their use, since it reduces the energy density of the cell. Recently, it has been shown that the stability of the potential window of aqueous electrolytes can be expanded by modifying the surface chemistry of the porous carbon electrodes [3][4][5][6][7][8]. Another strategy for increasing the voltage of aqueous-based electrolytes is the use of asymmetric configuration in mass electrodes [9], being optimized from the balance of charge by using the maximum allowable potential window of each electrode [10].…”
Section: Introductionmentioning
confidence: 99%
“…[74] In this section, post-synthesis is also summarized including: i) chemical methods [143][144][145] such as oxidation, fluorination and ii) electrochemical methods. [146][147][148][149] Herein, synthetic methods of zeolite-templated nanocarbons are discussed from the aspects of: i) CVD, ii) in situ pyrolysis, iii) solvothermal synthesis, and iv) post-synthesis.…”
Section: Synthetic Methodsmentioning
confidence: 99%